Real Options and Project Evaluation : A Primer - Knudsen, Odin K. (World Bank, Washington, DC, 2017)
In this paper authors present a preliminary approach to the evaluation of policies and projects based on current thinking on cost benefit analysis and real option methodology and the authors' recent work on the same subject. Authors start from the assumption that economic agents undertake investment projects in order to create and exploit opportunities for increasing profits, growth, wealth and, ultimately, their welfare. These opportunities are options, rights and not obligations to take some action in the future. They include not only projects undertaken, but also projects that could be adopted in the future and opportunities that can be further created or destroyed by this adoption. From the point of view of the welfare of an entire economy, opportunities enlarge the set of actions that may contribute to national wealth. Not only is this increased by the net flow of discounted benefits generated by new ventures, but also by the net value of the options created and destroyed by investment behavior. When companies develop investment opportunities, therefore, they contribute to national welfare in a more subtle, but not less important way, than when they are actively set to exploit some of these opportunities. By recognizing the direct contribution to country wealth of project design and planning, option theory may thus substantially change the theory and practice of decision making about capital investment.